Potassium Deficiency in Rice Aggravates Sarocladium oryzae Infection and Ultimately Leads to Alterations in Endophyte Communities and Suppression of Nutrient Uptake - Zhang, Jianglin; Lu, Zhifeng; Cong, Rihuan; Ren, Tao; Lu, Jianwei; Li, Xiaokun (Frontiers in Plant Science, 2022)
Sheath rot disease is an emerging fungal disease in rice, whose infection causes severe yield loss. Sarocladium oryzae (S. oryzae) is the major causal agent. Previous study has demonstrated that rice deficiency in potassium (K) aggravates S. oryzae infection. However, the effects of S. oryzae infection on the nutrient uptake process, endophyte communities and hormone level of host plant under K deficiency condition remain unclear, the mechanism of K mediated S. oryzae infection needs to be further study. The present study analyzed alterations in the endophytic community and nutrient-uptake process of host plants through an exogenous inoculation of S. oryzae in pot and hydroponics experiments. S. oryzae infection sharply increased the relative abundance of Ascomycota and decreased the Shannon and Simpson index of the endophytic community. Compared with the K-sufficient rice infected with S. oryzae, K-starved rice infected with S. oryzae (-K+I) increased the relative abundance of Ascomycota in leaf sheaths by 52.3%. Likewise, the -K+I treatment significantly decreased the Shannon and Simpson indexes by 27.7% and 25.0%, respectively. Sufficient K supply increased the relative abundance of Pseudomonas spp. in the host plant. S. oryzae infection profoundly inhibited the nutrient uptake of the host plant. The accumulation of oleic acid and linoleic acid in diseased rice decreased the biosynthesis of jasmonic acid (JA), and the content of JA was lowest in the -K+I treatment, which suppressed K+ uptake. These results emphasize the importance of K in resistance to S. oryzae infection by modulating endophyte community diversity and enhancing the nutrient uptake capacity of the host plant.